2003
DOI: 10.1256/qj.02.98
|View full text |Cite
|
Sign up to set email alerts
|

Propagation properties of inertia–gravity waves through a barotropic shear layer and application to the Antarctic polar vortex

Abstract: SUMMARYThe propagation of inertia-gravity waves (IGWs) through a dynamical transport barrier, such as the Antarctic polar vortex edge is investigated using a linear wave model. The model is based on the linearized, inviscid hydrostatic equations on an f -plane. Typical values for the parameters that are appropriate to the Antarctic polar vortex are given. The background ow U is assumed to be barotropic and its horizontal shear is represented by a hyperbolic tangent background wind pro le. The wave equation tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Notably, resonant over-reflection was not found by Ollers et al in [69] even though their scattering problem is similar to the one we study in Chapter 4 (and we observe the phenomenon there). We attribute this to the fact that Ollers et al …”
Section: The Phenomenon Of Resonant Over-reflection Was Introduced Insupporting
confidence: 88%
See 2 more Smart Citations
“…Notably, resonant over-reflection was not found by Ollers et al in [69] even though their scattering problem is similar to the one we study in Chapter 4 (and we observe the phenomenon there). We attribute this to the fact that Ollers et al …”
Section: The Phenomenon Of Resonant Over-reflection Was Introduced Insupporting
confidence: 88%
“…• For the model 3, Ollers et al [69] also tried to relate the results of the scattering problem with the condition for a zonal shear flow on the f -plane to be inertially unstable: f (U y − f ) > 0 is fulfilled somewhere in the flow (see Holton [34]). They found that when this condition is satisfied at the critical layer of the incident wave, then over-reflection is favoured although absorption is possible too.…”
Section: Thesis Outlinementioning
confidence: 99%
See 1 more Smart Citation